Antistatic adhesive for curved glass and production process thereof

By using modified polyurethane and other specific additives in curved glass adhesives, an interpenetrating mesh structure polymerized under light is formed, which solves the problems of poor antistatic effect and low bonding strength of curved glass adhesives, significantly improves adhesion and conductivity, and enhances the reliability and safety of electronic products.

CN119592268AInactive Publication Date: 2025-03-11DONGGUAN XINXING TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411652137.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-03-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

At this stage, the adhesives for curved glass have poor antistatic effects and low bonding strength, which may damage electronic components in dry or low humidity environments, affecting the reliability and safety of electronic products.

Method used

An antistatic adhesive for curved glass including modified polyurethane, hydroxyethyl acrylate, methacryloyloxyethyl trimethylammonium chloride, gamma-methacryloyloxypropyl trimethoxysilane, photoinitiator and DMF is used to form a modified polyurethane through modified monomer chain extension and hydroxyethyl acrylate terminal blocking, and polymerization is promoted by photoinitiator under light to form an interpenetrating grid structure to enhance adhesion and conductivity.

Benefits of technology

The adhesive forms an interpenetrating mesh structure under light, which significantly improves the adhesion and conductivity of curved glass, effectively prevents static electricity accumulation, and enhances the reliability and safety of electronic products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses an antistatic adhesive for curved glass and a production process of the antistatic adhesive. The antistatic adhesive is prepared from the following raw materials in parts by weight: 80 to 100 parts of modified polyurethane, 30 to 40 parts of hydroxyethyl acrylate, 10 to 15 parts of methacryloyloxyethyl trimethyl ammonium chloride, 5 to 10 parts of gamma-methacryloyloxypropyltrimethoxysilane, 1 to 1.5 parts of a photoinitiator and 40 to 50 parts of DMF (Dimethyl Formamide), siloxane on gamma-methacryloyloxy propyl trimethoxy silane can generate silanol groups when making contact with moisture in air, then the bonding force of the adhesive and glass is increased, hydroxyethyl acrylate is a hydrophilic group, the hydrophilic group can absorb moisture to form a conducting layer, quaternary ammonium salt side chains are contained, and therefore the conducting layer can absorb the moisture to form a conducting layer. The quaternary ammonium ions can provide freely moving ions on the surface of the adhesive, so that the ionic conductivity of the material is improved, and meanwhile, the modified polyurethane side chain contains polyaniline and electron donating groups, so that the conductivity of the material is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of glass adhesive preparation, and in particular to an antistatic adhesive for curved glass and a production process thereof. Background Art

[0002] With the popularity of smart electronic products such as smartphones and tablets, curved glass is widely used in front covers or screen protection of these mobile devices due to its unique visual effects and excellent grip comfort. This design significantly improves the user experience, but it also brings many challenges. Among them, how to ensure a good capacitive connection between the curved glass surface and the internal structure is one of the key issues. UV curing adhesives are a commonly used connection method. Traditional adhesives often generate static charges, especially in dry or low humidity environments, which may damage electronic components and cause abnormal operation or even equipment failure. Therefore, in order to prevent damage caused by static electricity accumulation and ensure the reliability and safety of electronic products, it has become an inevitable trend to develop new adhesives that can effectively eliminate or control static electricity. Summary of the invention

[0003] The purpose of the present invention is to provide an antistatic adhesive for curved glass and a production process thereof, which solves the problems that the current adhesive has poor antistatic effect and low bonding strength.

[0004] The purpose of the present invention can be achieved through the following technical solutions: A production process of an antistatic adhesive for curved glass, specifically comprising the following steps: Step A1: uniformly mix polypropylene glycol and isophorone diisocyanate, stir and add modified monomer at a speed of 120-150 r / min and a temperature of 20-25° C., react for 30-40 min, add hydroxyethyl acrylate, and continue to react for 30-40 min to obtain a polyurethane prepolymer, uniformly mix the polyurethane prepolymer and DMF, stir and add ammonium persulfate and aniline at a speed of 60-80 r / min, a temperature of 10-15° C. and a pH value of 1-2, and react for 20-25 h to obtain a modified polyurethane; Step A2: Weigh the following raw materials in parts by weight: 80-100 parts of modified polyurethane, 30-40 parts of hydroxyethyl acrylate, 10-15 parts of methacryloyloxyethyltrimethylammonium chloride, 5-10 parts of γ-methacryloyloxypropyltrimethoxysilane, 1-1.5 parts of photoinitiator and 40-50 parts of DMF, mix the raw materials evenly to obtain an antistatic adhesive for curved glass.

[0005] Furthermore, the mass ratio of the polypropylene glycol, isophorone diisocyanate, modified monomer and hydroxyethyl acrylate described in step A1 is 12:30:50:5, the mass fraction of polypropylene glycol is 2000, the mass ratio of the polyurethane prepolymer and aniline is 10:1, and the amount of potassium persulfate is 5‰ of the mass of aniline.

[0006] Further, the modified monomer is prepared by the following steps: Step B1: Tetramethylcyclotetrasiloxane, tridecafluorohexylethylene, chloroplatinic acid and DMF are mixed uniformly, nitrogen is introduced for protection, and the reaction is carried out for 3-5 hours at a speed of 150-200 r / min and a temperature of 60-70° C. to obtain intermediate 1; 4-hydroxyphthalic anhydride and DMF are mixed uniformly, and aniline is added under stirring at a speed of 120-150 r / min and a temperature of 0° C. to react for 1-1.5 hours, and the temperature is raised to 60-65° C., triethylamine, acetic anhydride and nickel acetate are added, and the reaction is continued for 2-3 hours to obtain intermediate 2; Step B2: γ-chloropropylheptamethylcyclotetrasiloxane, intermediate 2, potassium carbonate and DMF are mixed uniformly, and reacted at a speed of 200-300 r / min and a temperature of 70-75° C. for 10-15 hours to obtain intermediate 3; octamethylcyclotetrasiloxane, intermediate 1, intermediate 3, tetramethylammonium hydroxide, tetramethyldisiloxane and dimethyl sulfoxide are mixed uniformly, nitrogen is introduced for protection, and reacted at a speed of 120-150 r / min and a temperature of 105-110° C. for 3-5 hours to obtain polysiloxane; Step B3: 4-vinylbenzaldehyde, N,N'-dimethylethylenediamine, copper trifluoromethanesulfonate and deionized water are mixed, stirred for 10-15 minutes at a speed of 120-150 r / min and a temperature of 20-25°C to obtain a capping agent, polysiloxane, castor oil, chloroplatinic acid and DMF are mixed evenly, nitrogen is introduced for protection, and the reaction is carried out for 4-6 hours at a speed of 120-150 r / min and a temperature of 70-75°C, and the capping agent is added, and the reaction is continued for 3-5 hours to obtain a modified monomer.

[0007] Furthermore, the molar ratio of tetramethylcyclotetrasiloxane and tridecafluorohexylethylene described in step B1 is 1:4, the amount of chloroplatinic acid used is 1‰ of tridecafluorohexylethylene, and the amount ratio of 4-hydroxyphthalic anhydride, DMF, aniline, triethylamine, acetic anhydride and nickel acetate is 50mmol:50mL:50mmol:5mL:12mL:3.5g.

[0008] Furthermore, the molar ratio of γ-chloropropylheptamethylcyclotetrasiloxane, intermediate 2 and potassium carbonate in step B2 is 1:1:1.1, and the molar ratio of octamethylcyclotetrasiloxane, intermediate 1, intermediate 3, tetramethylammonium hydroxide and tetramethyldisiloxane is 1.4:0.5:0.5:3:2.

[0009] Furthermore, the amount ratio of 4-vinylbenzaldehyde, N,N'-dimethylethylenediamine, copper trifluoromethanesulfonate and deionized water in step B3 is 1mmol:1.2mmol:1mmol:75mL, and the molar ratio of Si-H bonds on polysiloxane, castor oil and capping agent is 2n+1:n:n+2, where n is a natural number greater than 1.

[0010] Beneficial effects of the invention: The application discloses an antistatic adhesive for curved glass, which comprises the following raw materials: modified polyurethane, hydroxyethyl acrylate, methacryloyloxyethyl trimethylammonium chloride, γ-methacryloyloxypropyl trimethoxysilane, a photoinitiator and DMF; a polyurethane prepolymer is prepared by reacting polypropylene glycol and isophorone diisocyanate as raw materials, and the chain is extended by using a modified monomer, and the polyurethane prepolymer is terminated by hydroxyethyl acrylate; the polyurethane prepolymer is reacted with aniline to form a polyaniline structure in the side chain of the polyurethane prepolymer to prepare the modified polyurethane.

[0011] The modified monomer uses tetramethylcyclotetrasiloxane and tridecafluorohexylethylene as raw materials. Under the action of chloroplatinic acid, the Si-H bond on the tetramethylcyclotetrasiloxane reacts with the double bond on the tridecafluorohexylethylene to obtain intermediate 1. 4-hydroxyphthalic anhydride and aniline react, so that the anhydride group on the 4-hydroxyphthalic anhydride reacts with the amino group on the aniline to obtain intermediate 2. γ-chloropropylheptamethylcyclotetrasiloxane and intermediate 2 react under the action of potassium carbonate to make the chlorine atom site on the γ-chloropropylheptamethylcyclotetrasiloxane and the phenolic hydroxyl group on the intermediate 2 to obtain the intermediate 3, the octamethylcyclotetrasiloxane, the intermediate 1 and the intermediate 3 are ring-opened, and then polymerized with tetramethyldisiloxane to obtain polysiloxane, 4-vinylbenzaldehyde and N,N'-dimethylethylenediamine react to form a five-membered ring structure to obtain a capping agent, the polysiloxane and castor oil are reacted under the action of chloroplatinic acid so that the Si-H bond on the polysiloxane reacts with the double bond on the castor oil, and the Si-H capped branched structure is formed by controlling the dosage, and then the capping agent is used to cap the end to obtain a modified monomer.

[0012] When the adhesive is exposed to light, the photoinitiator promotes the polymerization of modified polyurethane, hydroxyethyl acrylate, methacryloyloxyethyl trimethylammonium chloride and γ-methacryloxypropyl trimethoxysilane to form an interpenetrating grid structure. The siloxane on γ-methacryloxypropyl trimethoxysilane can produce silanol groups when it comes into contact with moisture in the air, thereby increasing the adhesion between the adhesive and the glass. Hydroxyethyl acrylate is a hydrophilic group that absorbs moisture to form a conductive layer and contains quaternary ammonium salt side chains. Quaternary ammonium ions can provide freely moving ions on the surface of the adhesive, thereby increasing the ionic conductivity of the material. At the same time, the modified polyurethane side chains contain polyaniline and electron-donating groups, which greatly improve the conductivity of the material. DETAILED DESCRIPTION

[0013] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example

[0014] A production process of an antistatic adhesive for curved glass, specifically comprising the following steps: Step A1: polypropylene glycol and isophorone diisocyanate are mixed evenly, and the modified monomer is added under the conditions of a rotation speed of 120 r / min and a temperature of 20° C., and the reaction is carried out for 30 minutes, and then hydroxyethyl acrylate is added, and the reaction is continued for 30 minutes to obtain a polyurethane prepolymer, and the polyurethane prepolymer and DMF are mixed evenly, and ammonium persulfate and aniline are added under the conditions of a rotation speed of 60-80 r / min, a temperature of 10-15° C., and a pH value of 1-2, and the reaction is carried out for 20-25 hours to obtain a modified polyurethane; Step A2: Weigh the following raw materials in parts by weight: 80 parts of modified polyurethane, 30 parts of hydroxyethyl acrylate, 10 parts of methacryloyloxyethyltrimethylammonium chloride, 5 parts of γ-methacryloyloxypropyltrimethoxysilane, 1 part of photoinitiator and 40 parts of DMF, mix the raw materials evenly to obtain an antistatic adhesive for curved glass.

[0015] The mass ratio of the polypropylene glycol, isophorone diisocyanate, modified monomer and hydroxyethyl acrylate described in step A1 is 12:30:50:5, the mass fraction of polypropylene glycol is 2000, the mass ratio of the polyurethane prepolymer and aniline is 10:1, and the amount of potassium persulfate used is 5‰ of the mass of aniline.

[0016] The photoinitiator described in step A2 is Irgacure 184D.

[0017] The modified monomer is prepared by the following steps: Step B1: Tetramethylcyclotetrasiloxane, tridecafluorohexylethylene, chloroplatinic acid and DMF are mixed evenly, nitrogen is introduced for protection, and the reaction is carried out for 3 hours at a speed of 150 r / min and a temperature of 60°C to obtain intermediate 1. 4-Hydroxyphthalic anhydride and DMF are mixed evenly, and aniline is added under stirring at a speed of 120 r / min and a temperature of 0°C to react for 1 hour, and the temperature is raised to 60°C, triethylamine, acetic anhydride and nickel acetate are added, and the reaction is continued for 2 hours to obtain intermediate 2; Step B2: γ-chloropropylheptamethylcyclotetrasiloxane, intermediate 2, potassium carbonate and DMF are mixed uniformly, and reacted at a speed of 200 r / min and a temperature of 70° C. for 10 hours to obtain intermediate 3; octamethylcyclotetrasiloxane, intermediate 1, intermediate 3, tetramethylammonium hydroxide, tetramethyldisiloxane and dimethyl sulfoxide are mixed uniformly, nitrogen is introduced for protection, and reacted at a speed of 120 r / min and a temperature of 105° C. for 3 hours to obtain polysiloxane; Step B3: 4-vinylbenzaldehyde, N,N'-dimethylethylenediamine, copper trifluoromethanesulfonate and deionized water are mixed, and stirred for 10 minutes at a speed of 120 r / min and a temperature of 20°C to obtain a capping agent. Polysiloxane, castor oil, chloroplatinic acid and DMF are mixed evenly, and nitrogen is introduced for protection. The reaction is carried out at a speed of 120 r / min and a temperature of 70°C for 4 hours. The capping agent is added and the reaction is continued for 3 hours to obtain a modified monomer.

[0018] The molar ratio of tetramethylcyclotetrasiloxane and tridecafluorohexylethylene described in step B1 is 1:4, the amount of chloroplatinic acid used is 1‰ of tridecafluorohexylethylene, and the amount ratio of 4-hydroxyphthalic anhydride, DMF, aniline, triethylamine, acetic anhydride and nickel acetate is 50mmol:50mL:50mmol:5mL:12mL:3.5g.

[0019] The molar ratio of γ-chloropropylheptamethylcyclotetrasiloxane, intermediate 2 and potassium carbonate described in step B2 is 1:1:1.1, and the molar ratio of octamethylcyclotetrasiloxane, intermediate 1, intermediate 3, tetramethylammonium hydroxide and tetramethyldisiloxane is 1.4:0.5:0.5:3:2.

[0020] The amount ratio of 4-vinylbenzaldehyde, N,N'-dimethylethylenediamine, copper trifluoromethanesulfonate and deionized water in step B3 is 1mmol:1.2mmol:1mmol:75mL, and the molar ratio of Si-H bonds on polysiloxane, castor oil and capping agent is 3:1:3. Example

[0021] A production process of an antistatic adhesive for curved glass, specifically comprising the following steps: Step A1: polypropylene glycol and isophorone diisocyanate are mixed evenly, and the modified monomer is added under the conditions of a rotation speed of 120 r / min and a temperature of 25° C., and the reaction is carried out for 35 minutes, and then hydroxyethyl acrylate is added, and the reaction is continued for 35 minutes to obtain a polyurethane prepolymer, and the polyurethane prepolymer and DMF are mixed evenly, and ammonium persulfate and aniline are added under the conditions of a rotation speed of 60-80 r / min, a temperature of 10-15° C., and a pH value of 1-2, and the reaction is carried out for 20-25 hours to obtain a modified polyurethane; Step A2: Weigh the following raw materials in parts by weight: 90 parts of modified polyurethane, 35 parts of hydroxyethyl acrylate, 13 parts of methacryloyloxyethyltrimethylammonium chloride, 8 parts of γ-methacryloyloxypropyltrimethoxysilane, 1.2 parts of photoinitiator and 45 parts of DMF, mix the raw materials evenly to obtain an antistatic adhesive for curved glass.

[0022] The mass ratio of the polypropylene glycol, isophorone diisocyanate, modified monomer and hydroxyethyl acrylate described in step A1 is 12:30:50:5, the mass fraction of polypropylene glycol is 2000, the mass ratio of the polyurethane prepolymer and aniline is 10:1, and the amount of potassium persulfate used is 5‰ of the mass of aniline.

[0023] The photoinitiator described in step A2 is 1173.

[0024] The modified monomer is prepared by the following steps: Step B1: Tetramethylcyclotetrasiloxane, tridecafluorohexylethylene, chloroplatinic acid and DMF were mixed evenly, nitrogen was introduced for protection, and the reaction was carried out for 4 hours at a speed of 150 r / min and a temperature of 65°C to obtain intermediate 1. 4-Hydroxyphthalic anhydride and DMF were mixed evenly, and aniline was added under stirring at a speed of 150 r / min and a temperature of 0°C to react for 1.5 hours, and the temperature was raised to 60°C, triethylamine, acetic anhydride and nickel acetate were added, and the reaction was continued for 2.5 hours to obtain intermediate 2; Step B2: γ-chloropropylheptamethylcyclotetrasiloxane, intermediate 2, potassium carbonate and DMF are mixed uniformly, and reacted at a speed of 300 r / min and a temperature of 70°C for 15 hours to obtain intermediate 3; octamethylcyclotetrasiloxane, intermediate 1, intermediate 3, tetramethylammonium hydroxide, tetramethyldisiloxane and dimethyl sulfoxide are mixed uniformly, nitrogen is introduced for protection, and reacted at a speed of 120 r / min and a temperature of 110°C for 4 hours to obtain polysiloxane; Step B3: 4-vinylbenzaldehyde, N,N'-dimethylethylenediamine, copper trifluoromethanesulfonate and deionized water are mixed, and stirred for 10 minutes at a speed of 120 r / min and a temperature of 25°C to obtain a capping agent. Polysiloxane, castor oil, chloroplatinic acid and DMF are mixed evenly, and nitrogen is introduced for protection. The reaction is carried out at a speed of 120 r / min and a temperature of 75°C for 5 hours. The capping agent is added and the reaction is continued for 4 hours to obtain a modified monomer.

[0025] The molar ratio of tetramethylcyclotetrasiloxane and tridecafluorohexylethylene described in step B1 is 1:4, the amount of chloroplatinic acid used is 1‰ of tridecafluorohexylethylene, and the amount ratio of 4-hydroxyphthalic anhydride, DMF, aniline, triethylamine, acetic anhydride and nickel acetate is 50mmol:50mL:50mmol:5mL:12mL:3.5g.

[0026] The molar ratio of γ-chloropropylheptamethylcyclotetrasiloxane, intermediate 2 and potassium carbonate described in step B2 is 1:1:1.1, and the molar ratio of octamethylcyclotetrasiloxane, intermediate 1, intermediate 3, tetramethylammonium hydroxide and tetramethyldisiloxane is 1.4:0.5:0.5:3:2.

[0027] The amount ratio of 4-vinylbenzaldehyde, N,N'-dimethylethylenediamine, copper trifluoromethanesulfonate and deionized water in step B3 is 1mmol:1.2mmol:1mmol:75mL, and the molar ratio of Si-H bonds on polysiloxane, castor oil and capping agent is 5:2:4. Example

[0028] A production process of an antistatic adhesive for curved glass, specifically comprising the following steps: Step A1: polypropylene glycol and isophorone diisocyanate are mixed evenly, and the modified monomer is added under the conditions of a rotation speed of 150 r / min and a temperature of 25° C., and the reaction is carried out for 40 minutes, and then hydroxyethyl acrylate is added, and the reaction is continued for 40 minutes to obtain a polyurethane prepolymer, and the polyurethane prepolymer and DMF are mixed evenly, and ammonium persulfate and aniline are added under the conditions of a rotation speed of 60-80 r / min, a temperature of 10-15° C., and a pH value of 1-2, and the reaction is carried out for 20-25 hours to obtain a modified polyurethane; Step A2: Weigh the following raw materials in parts by weight: 100 parts of modified polyurethane, 40 parts of hydroxyethyl acrylate, 15 parts of methacryloyloxyethyltrimethylammonium chloride, 10 parts of γ-methacryloyloxypropyltrimethoxysilane, 1.5 parts of photoinitiator and 50 parts of DMF, mix the raw materials evenly to obtain an antistatic adhesive for curved glass.

[0029] The mass ratio of the polypropylene glycol, isophorone diisocyanate, modified monomer and hydroxyethyl acrylate described in step A1 is 12:30:50:5, the mass fraction of polypropylene glycol is 2000, the mass ratio of the polyurethane prepolymer and aniline is 10:1, and the amount of potassium persulfate used is 5‰ of the mass of aniline.

[0030] The photoinitiator described in step A2 is Lencolo5030.

[0031] The modified monomer is prepared by the following steps: Step B1: Tetramethylcyclotetrasiloxane, tridecafluorohexylethylene, chloroplatinic acid and DMF were mixed evenly, nitrogen was introduced for protection, and the reaction was carried out for 5 hours at a speed of 200 r / min and a temperature of 70°C to obtain intermediate 1. 4-Hydroxyphthalic anhydride and DMF were mixed evenly, and aniline was added under stirring at a speed of 150 r / min and a temperature of 0°C to react for 1.5 hours, and the temperature was raised to 65°C, triethylamine, acetic anhydride and nickel acetate were added, and the reaction was continued for 3 hours to obtain intermediate 2; Step B2: γ-chloropropylheptamethylcyclotetrasiloxane, intermediate 2, potassium carbonate and DMF were mixed uniformly, and reacted at a speed of 300 r / min and a temperature of 75°C for 15 hours to obtain intermediate 3; octamethylcyclotetrasiloxane, intermediate 1, intermediate 3, tetramethylammonium hydroxide, tetramethyldisiloxane and dimethyl sulfoxide were mixed uniformly, nitrogen was introduced for protection, and the reaction was carried out at a speed of 150 r / min and a temperature of 110°C for 5 hours to obtain polysiloxane; Step B3: 4-vinylbenzaldehyde, N,N'-dimethylethylenediamine, copper trifluoromethanesulfonate and deionized water are mixed, and stirred for 15 minutes at a speed of 150 r / min and a temperature of 25°C to obtain a capping agent. Polysiloxane, castor oil, chloroplatinic acid and DMF are mixed evenly, and nitrogen is introduced for protection. The reaction is carried out at a speed of 150 r / min and a temperature of 75°C for 6 hours. The capping agent is added and the reaction is continued for 5 hours to obtain a modified monomer.

[0032] The molar ratio of tetramethylcyclotetrasiloxane and tridecafluorohexylethylene described in step B1 is 1:4, the amount of chloroplatinic acid used is 1‰ of tridecafluorohexylethylene, and the amount ratio of 4-hydroxyphthalic anhydride, DMF, aniline, triethylamine, acetic anhydride and nickel acetate is 50mmol:50mL:50mmol:5mL:12mL:3.5g.

[0033] The molar ratio of γ-chloropropylheptamethylcyclotetrasiloxane, intermediate 2 and potassium carbonate described in step B2 is 1:1:1.1, and the molar ratio of octamethylcyclotetrasiloxane, intermediate 1, intermediate 3, tetramethylammonium hydroxide and tetramethyldisiloxane is 1.4:0.5:0.5:3:2.

[0034] The amount ratio of 4-vinylbenzaldehyde, N,N'-dimethylethylenediamine, copper trifluoromethanesulfonate and deionized water in step B3 is 1mmol:1.2mmol:1mmol:75mL, and the molar ratio of Si-H bonds on polysiloxane, castor oil and capping agent is 7:3:5.

[0035] Comparative Example 1 Compared with Example 1, methacryloyloxyethyl trimethyl ammonium chloride was not added in this comparative example, and the remaining steps were the same.

[0036] Comparative Example 2 Compared with Example 1, in this comparative example, polysiloxane, allyl alcohol, chloroplatinic acid and DMF are uniformly mixed, nitrogen is introduced for protection, and the reaction is carried out for 4 hours at a speed of 120 r / min and a temperature of 70° C. The obtained product replaces the modified monomer, and the remaining steps are the same.

[0037] Comparative Example 3 Compared with Example 1, this comparative example did not add intermediate 3, and the remaining steps were the same.

[0038] The adhesives prepared in Examples 1-3 and Comparative Examples 1-3 were tested for volume resistivity according to the standard of GB / T1410-2006, and for tensile shear strength of adhesives according to the national standard GB / T7124-2008 (rigid material to rigid material). According to the actual use of the present invention, a glass test piece with a length×width×thickness of 76.2mm×25.4mm×1.2mm was used as the adhesive for polishing and fixing frosted glass of the present invention for bonding (bonding overlap length of 10mm), and the test results are shown in the following table.

[0039]

[0040] It can be seen from the above table that the present invention has good antistatic and bonding effects.

[0041] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A production process of an antistatic adhesive for curved glass, characterized in that: The specific steps include: Step A1: polypropylene glycol and isophorone diisocyanate are mixed and stirred, and a modified monomer is added to react, and then hydroxyethyl acrylate is added to continue the reaction to obtain a polyurethane prepolymer, and the polyurethane prepolymer and DMF are mixed and stirred, and ammonium persulfate and aniline are added to react to obtain a modified polyurethane; Step A2: Weigh the following raw materials in parts by weight: 80-100 parts of modified polyurethane, 30-40 parts of hydroxyethyl acrylate, 10-15 parts of methacryloyloxyethyltrimethylammonium chloride, 5-10 parts of γ-methacryloyloxypropyltrimethoxysilane, 1-1.5 parts of photoinitiator and 40-50 parts of DMF, mix the raw materials evenly to obtain an antistatic adhesive for curved glass.

2. The production process of an antistatic adhesive for curved glass according to claim 1, characterized in that: The mass ratio of the polypropylene glycol, isophorone diisocyanate, modified monomer and hydroxyethyl acrylate described in step A1 is 12:30:50:5, and the mass ratio of the polyurethane prepolymer and aniline is 10:

1.

3. The production process of an antistatic adhesive for curved glass according to claim 1, characterized in that: The modified monomer is prepared by the following steps: Step B1: Tetramethylcyclotetrasiloxane, tridecafluorohexylethylene, chloroplatinic acid and DMF are uniformly mixed, nitrogen is introduced for protection, and the reaction is carried out to obtain intermediate 1; 4-hydroxyphthalic anhydride and DMF are uniformly mixed, aniline is added after stirring, and the reaction is carried out; the temperature is increased and triethylamine, acetic anhydride and nickel acetate are added, and the reaction is continued to obtain intermediate 2; Step B2: γ-chloropropylheptamethylcyclotetrasiloxane, intermediate 2, potassium carbonate and DMF are mixed to react to obtain intermediate 3, octamethylcyclotetrasiloxane, intermediate 1, intermediate 3, tetramethylammonium hydroxide, tetramethyldisiloxane and dimethyl sulfoxide are mixed uniformly, nitrogen is introduced for protection, and the reaction is carried out to obtain polysiloxane; Step B3: 4-vinylbenzaldehyde, N,N'-dimethylethylenediamine, copper trifluoromethanesulfonate and deionized water are mixed and stirred to prepare a capping agent, polysiloxane, castor oil, chloroplatinic acid and DMF are mixed evenly, nitrogen is introduced to protect, the capping agent is added, and the reaction is continued to prepare a modified monomer.

4. The production process of an antistatic adhesive for curved glass according to claim 1, characterized in that: The molar ratio of tetramethylcyclotetrasiloxane and tridecafluorohexylethylene described in step B1 is 1:4, and the usage ratio of 4-hydroxyphthalic anhydride, DMF, aniline, triethylamine, acetic anhydride and nickel acetate is 50mmol:50mL:50mmol:5mL:12mL:3.5g.

5. The production process of an antistatic adhesive for curved glass according to claim 1, characterized in that: The molar ratio of γ-chloropropylheptamethylcyclotetrasiloxane, intermediate 2 and potassium carbonate described in step B2 is 1:1:1.1, and the molar ratio of octamethylcyclotetrasiloxane, intermediate 1, intermediate 3, tetramethylammonium hydroxide and tetramethyldisiloxane is 1.4:0.5:0.5:3:

2.

6. The production process of an antistatic adhesive for curved glass according to claim 1, characterized in that: The amount ratio of 4-vinylbenzaldehyde, N,N'-dimethylethylenediamine, copper trifluoromethanesulfonate and deionized water in step B3 is 1mmol:1.2mmol:1mmol:75mL, and the molar ratio of Si-H bonds on polysiloxane, castor oil and capping agent is 2n+1:n:n+2, where n is a natural number greater than 1.

7. An antistatic adhesive for curved glass, characterized in that: Produced according to any one of the production processes described in claims 1-6.